2019
DOI: 10.3390/cells8020146
|View full text |Cite
|
Sign up to set email alerts
|

Focus on Cdc42 in Breast Cancer: New Insights, Target Therapy Development and Non-Coding RNAs

Abstract: Breast cancer is the most common malignant tumors in females. Although the conventional treatment has demonstrated a certain effect, some limitations still exist. The Rho guanosine triphosphatase (GTPase) Cdc42 (Cell division control protein 42 homolog) is often upregulated by some cell surface receptors and oncogenes in breast cancer. Cdc42 switches from inactive guanosine diphosphate (GDP)-bound to active GTP-bound though guanine-nucleotide-exchange factors (GEFs), results in activation of signaling cascades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 188 publications
2
33
0
Order By: Relevance
“…MMP9 expression levels were positively associated with the expression of CDC42. CDC42 is a member of the Rho family of GTPases, which plays a role in many of the cellular processes that are associated with tumour progression, such as cell migration, proliferation, cytoskeletal control and vesicular trafficking [44]. A study conducted by Sipes and colleagues; revealed that, CDC42 deletion significantly reduced MMP9 activity.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 expression levels were positively associated with the expression of CDC42. CDC42 is a member of the Rho family of GTPases, which plays a role in many of the cellular processes that are associated with tumour progression, such as cell migration, proliferation, cytoskeletal control and vesicular trafficking [44]. A study conducted by Sipes and colleagues; revealed that, CDC42 deletion significantly reduced MMP9 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Besides being a predictive factor for tumor occurrence or for its progression, whether Rho GTPases pathways could be used as therapeutic targets is clearly an aspect that needs to be developed in the near future. Several drugs directly targeting Rho GTPases have been recently designed and different strategies such as preventing Rho GEF interaction or inhibiting effectors have been proposed [125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141]. However, based on the complex involvement of Rho GTPases and their regulators in NETs hypersecretion, as reviewed here, the development of proper strategies to target each specific tumor will be critical and will require a perfect knowledge of the mechanisms leading to the deregulation of the Rho pathways, as well as their consequences on tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Metastasis is a key factor influencing the prognosis of PC, and it is well-known that miRNAs can regulate the development, progression and metastasis of breast cancer ( 33 , 34 ). In PC, miRNAs have been found to affect tumor metastasis and function as biomarkers, and prognostic and therapeutic modulators of PC ( 35 38 ).…”
Section: Discussionmentioning
confidence: 99%